MANAJEMEN RISIKO PEMBIBITAN KOPI ARABIKA LS 795 (Studi Kasus Kebun Dinas Sukajadi, Kecamatan Wado, Kabupaten Sumedang) - Kreshtanti Ericha Pramesti; Pandi Pardian (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
Sukajadi official garden is the only one of the government institutions in west java that produces LS 795 arabica coffee seeds and placed at Sumedang regency. In the process of coffee seed production, that various risks affect the optimization of production results. The seedling period is the most important part of coffee growth because good quality seeds will produce coffee cherries with good quantity and quality as well. This research aims to identify the risks that occur and identify risk management strategies in the LS 795 Arabica coffee nursery activity at the Sukajadi Official Garden. Data analysis in this research used a qualitative descriptive method with case study research techniques. The analytical tool used in this research is the House of Risk (HOR) stages 1 and 2. The results show that there are seven stages of LS 795 arabica coffee production, 26 risk events were identified and 25 risk sources, of which 10 risk sources were prioritized to be addressed first, and selected 7 of the 12 most appropriate mitigation actions to address priority risks.